Superconductivity and localization - Sadovskiĭ, M. V. (Mikhail Vissarionovich), 1948- (World Scientific, 2000)
"This book presents a review of theoretical and experimental work on the problem of the interplay of Anderson localization and superconductivity in strongly disordered systems. Superconductivity persists close to disorder-induced metal-insulator transition in a number of real systems, e.g. amorphous metals and compounds, systems disordered by fast neutron irradiation, systems with impurities, etc. High temperature superconductors are especially interesting from this point of view, as the experiments with controllable disordering may provide important clues to the nature of electronic states in these systems."--Jacket